Cyberloafing in Higher Education: Reasons and Suggestions from Students' Perspectives - Varol, Filiz; Yildirim, Esat (Springer, 2019)
The main goals of the current study are (1) college students' cyberloafing behaviors during a lab session, (2) reasons that students cyberloaf, and (3) possible solutions to prevent this behavior from the students' perspectives. A total of 184 students registered for lab hours at a public university in Turkey were recruited to participate in this qualitative study. They reported what type of cyberloafing behaviors they showed during lab hours. Data analysis were completed based on four main themes contributing to learners' cyberloafing: instructor, student, course content, and learning environment. In addition, participants were asked to provide suggestions. Once researchers understand the causes and preventative measures for cyberloafing at the college level, educators can provide better learning opportunities. Thus, the findings of this study can be applied to future research to diminish cyberloafing behaviors during lab sessions.
Keywords: Cyberloafing; Higher education; Qualitative; Motivation